Examining the uncovered equity parity in the emerging financial markets - Aftab, Muhammad; Ahmad, Rubi; Ismail, Izlin (Elsevier, 2018)
Uncovered Equity Parity condition states that the foreign equity market outperformance relative to the home equity market associates with foreign exchange rate depreciation. This study examines this condition in the emerging financial markets context using bounds testing approach to the level relations. Our rigorous analysis shows an evidence opposite to the UEP prediction such that an outperformance of foreign equity market links with a foreign exchange rate appreciation. Moreover, a nonlinear model shows an asymmetry in the equity market effect on the exchange rate, both in the short run and long run.